Building institutional synergies for agricultural research and development in Ghana: The case of the cropping calendar agro-advisory - Amankwaa-Yeboah, Patricia; Ofosu-Ampong, Kingsley; Masoud, Jalaludeen; Jizorkuwie, Abdul-latif Baamonyor; Wilson, Michael; Ampadu-Boakye, Theresa; Abera, Wuletawu (CGIAR, 2025)
In the face of climate variability, fragmented extension systems, and increasingly complex farming realities, Ghana’s agricultural transformation demands more than incremental change; it requires a paradigm shift in how knowledge is generated, delivered, and applied. This paper presents the co-development and early scaling of a dynamic cropping calendar and bundled agro-advisory tool, a partnership-driven innovation led by CSIR-INSTI, CSIR-CRI, CSIR-Soil Research Institute, the Ministry of Food and Agriculture (MoFA), and the Alliance of Bioversity International and CIAT, under the CGIAR Excellence in Agronomy Initiative. More than a scheduling tool, the system integrates real-time climate data, localised soil diagnostics, crop phenology, and behavioural insights to deliver timely, actionable, and site-specific crop production advisories. Guided by a multi-theoretical framework that encompasses human-centred design and participatory digital ecosystems theory, the initiative reimagines agricultural advisory services as adaptive, inclusive, and co-owned platforms for learning and decision-making. The system’s success stems from a uniquely integrated public–private–research partnership model, enabling institutional coordination, digital reach, and iterative field validation across Ghana’s diverse agroecologies. Through localised content delivery and recently embedded feedback loops, the Cropping calendar and bundled agro-advisory tool advance equity, resilience, and knowledge democratisation. This report demonstrates how partnerships and conceptual clarity can transform advisory services from static information transfer to dynamic, scalable, climate-smart, and farmer-responsive systems. The Ghanaian experience offers a replicable blueprint for modernising extension architectures, not only for national impact but also for regional adaptation and learning across sub-Saharan Africa.